Pengembangan Bahan Ajar E-Learning Berbasis Edmodo pada Materi FPB dan KPK Kelas 4 SD Negeri Jrahi 01 - Dian Ratna Suryandari; Riris Setyo Sundari; Wawan Priyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to determine the characteristics of the development of e-learning teaching materials on Edmodo-based FPB and KPK materials and to determine the validity and practicality of Edmodo-based e-learning teaching materials that will be developed. This type of research is research and development or Research and Development (R&D). The model used in this study is the 4D (four-D) model which consists of 4 stages, namely define, design, develop, and disseminate. Data collection was carried out through observation, interviews, questionnaires, and documentation. This research was conducted in grade 4 SD Negeri Jrahi 01, SD Negeri Jrahi 02, and SD Negeri Giling 03. The results of data analysis showed that the average result of the media validation questionnaire was 97% which means "can be used without revision", validation of material 92 % which means "can be used without revision", and practitioner validation is 95% which means "can be used without revision". While the average student response questionnaire results were 95.2%, which means "can be used without revision". The results showed that students liked Edmodo-based e-learning teaching materials because by using these teaching materials, students felt happy and enthusiastic about learning.